WNT10B/β‐catenin signalling induces HMGA2 and proliferation in metastatic triple‐negative breast cancer. Issue 2 (11th January 2013) - Wend, Peter; Runke, Stephanie; Wend, Korinna; Anchondo, Brenda; Yesayan, Maria; Jardon, Meghan; Hardie, Natalie; Loddenkemper, Christoph; Ulasov, Ilya; Lesniak, Maciej S.; Wolsky, Rebecca; Bentolila, Laurent A.; et al.
Abstract Wnt/β‐catenin signalling has been suggested to be active in basal‐like breast cancer. However, in highly aggressive metastatic triple‐negative breast cancers (TNBC) the role of β‐catenin and the underlying mechanism(s) for the aggressiveness of TNBC remain unknown. We illustrate that WNT10B induces transcriptionally active β‐catenin in human TNBC and predicts survival‐outcome of patients with both TNBC and basal‐like tumours. We provide evidence that transgenic murine Wnt10b‐driven tumours are devoid of ERα, PR and HER2 expression and can model human TNBC. Importantly, HMGA2 is specifically expressed during early stages of embryonic mammogenesis and absent when WNT10B expression is lost, suggesting a developmentally conserved mode of action. Mechanistically, ChIP analysis uncovered that WNT10B activates canonical β‐catenin signalling leading to up‐regulation of HMGA2. Treatment of mouse and human triple‐negative tumour cells with two Wnt/β‐catenin pathway modulators or siRNA to HMGA2 decreases HMGA2 levels and proliferation. We demonstrate that WNT10B has epistatic activity on HMGA2, which is necessary and sufficient for proliferation of TNBC cells. Furthermore, HMGA2 expression predicts relapse‐free‐survival and metastasis in TNBC patients.